2010
DOI: 10.1111/j.1600-6143.2010.03261.x
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of Methods to Grade Transplant Glomerulitis in Renal Allograft Biopsies

Abstract: Transplant glomerulitis is an increasingly recognized lesion in renal transplant biopsies. To develop a refined grading system, we defined glomerulitis by the presence of ≥5 leukocytes/glomerulus and evaluated 111 biopsies using three different grading systems: (i) percentage of glomerular involvement, (ii) peak inflammation in the most severely affected glomerulus and (iii) presence/absence of endocapillary occlusion by inflammatory cells. Endocapillary occlusion had no impact on graft survival, but was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 28 publications
(75 reference statements)
7
36
0
Order By: Relevance
“…Batal et al reported that glomerulitis is associated with higher ptc scores, C4d positivity, and subsequent development of DSA and TGP, but not with interstitial inflammation, tubulitis, intimal arteritis, or T cell-mediated acute rejection (27). The same group later documented higher intraglomerular and peritubular capillary granzyme B+ leukocytes in 25 biopsy specimens with glomerulitis (28).…”
Section: Discussionmentioning
confidence: 66%
“…Batal et al reported that glomerulitis is associated with higher ptc scores, C4d positivity, and subsequent development of DSA and TGP, but not with interstitial inflammation, tubulitis, intimal arteritis, or T cell-mediated acute rejection (27). The same group later documented higher intraglomerular and peritubular capillary granzyme B+ leukocytes in 25 biopsy specimens with glomerulitis (28).…”
Section: Discussionmentioning
confidence: 66%
“…Addition of CD68 staining did not improve inter-observer agreement when glomerulitis was scored using the definition that includes endothelial enlargement/capillary occlusion. Whether such agreement would be improved by addition of a threshold number of leukocytes/glomerulus to the current definition, as suggested by Batal et al (6), is an issue for future consideration.…”
Section: Findings Of Banff Renal Allograft Pathology Working Groupsmentioning
confidence: 92%
“…However, the new consensus guidelines should be used in routine assessment. The excellent work of Randhawa's group [9] for the definition of transplant glomerulitis can still be recommended. Another new and debatable addition to the criteria for acute antibody-mediated rejection is mRNA transcriptome expression analysis [5].…”
Section: Histopathological Diagnosis Of Acute Antibody-mediated Rejecmentioning
confidence: 99%